Transforming Social Studies Pedagogy: Artificial Intelligence-Based tool and Students’ Academic Performance in Ondo State, Nigeria - Alabi, Abidoye James; Adelekan, Akeem Tunde; Olotu, Gbenga (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study examined the transformation of social studies pedagogy through artificial intelligence-based tools and students’ academic performance in Ondo State, Nigeria. This study adopted a pre-test, post-test control group quasi-experimental research design. Three objectives were set for the study, and three research hypotheses were formulated to guide it. The population for the study consisted of all secondary students in Ondo State. The sample population comprised 163 Junior Secondary School (JSS II) students drawn from four public secondary schools randomly selected in the Ondo West Local Government Area of Ondo State, Nigeria. Two instruments were used in the study. They are the Social Studies Performance Test (SSPT) and the Modified Lesson Note (MLN). All the instruments were validated by experts. The reliability of the instrument (SSPT) was determined, and a reliability coefficient of 0.83 was obtained. Students' academic data was collected, and we analyzed covariances (ANCOVA). variance (ANCOVA). The social studies that students exposed to ITS demonstrated significantly higher academic performance than those taught by other methods (F (1,154) = 111.124, p < 0.05, partial η² = .419). The findings also revealed no significant effects of gender and school location on students' academic performance. This evidence suggests that intelligent tutoring systems (ITS) provide equitable learning opportunities. The study recommends increased investment in ICT infrastructure, teacher training, and policy interventions to enhance ITS integration into the teaching and learning of secondary schools’ subjects.